2013
DOI: 10.1007/s10834-013-9357-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Household Wealth Sustainable? An Examination of Asset Poverty Reentry After an Exit

Abstract: This paper analyzed the influence of financial behaviors on the duration out of asset poverty while controlling for households' life cycle and demographic characteristics. We found evidence for the existence of structural barriers to asset acquisition. Asset accumulation at or above levels equal to nine-months worth of income at the incomepoverty level was important for improving a household's odds of permanently escaping asset poverty, but a linear relationship between asset accumulation and the likelihood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This finding implies that we must consider the risks associated with more productive portfolio allocations; high ratio of productive asset can sometimes lead to an erosion in a household's assets (Leonard & Di, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding implies that we must consider the risks associated with more productive portfolio allocations; high ratio of productive asset can sometimes lead to an erosion in a household's assets (Leonard & Di, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, as previously mentioned, the risks and returns need to be properly balanced in household asset portfolio (Leonard & Di, 2013). Accordingly, the wide distribution of financial education programs among disadvantaged group is needed to encourage the asset poor to make prudent investment decisions and accumulate assets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The DHS protocol was approved by the institutional review boards at the University of Texas Southwestern Medical Center and the National Heart, Lung, and Blood Institute.…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, $5403 was needed for a three-month cushion and $10,806 was needed for a 6-month cushion. Leonard and Di (2014) found that asset accumulation at or above levels equal to 9 months' worth of income at the income-poverty level was important for improving a family's odds of escaping asset poverty. In 2007, when families in the lowest-income quintile were asked how much savings they believe they needed for emergencies and other contingencies, the median response was $2000, a value substantially less than what is needed to cover three months of expenses (Bucks et al 2009).…”
Section: Buffer-stock Savingmentioning
confidence: 99%